Critical decisions in the trauma intensive care unit: Are we practicing primary palliative care?. Issue 5 (23rd November 2021) - Edsall, Andrew; Howard, Shannon; Dewey, Elizabeth N.; Siegel, Timothy; Zonies, David; Brasel, Karen; Cook, Mackenzie R.; Nagengast, Andrea K.
Abstract : BACKGROUND: Devastating injuries require both urgent assessment by a trauma service and early attention to patients' goals of care (GOC). American College of Surgeons Trauma Quality Improvement Program (TQIP) guidelines recommend an initial palliative assessment within 24 hours of admission and family meeting, if needed, within 72 hours. We hypothesize that a primary palliative care–based practice improves adherence to TQIP guidelines in trauma patients. METHODS: All adult trauma patients who died while inpatient from January 2014 to December 2018 were reviewed. Timing of GOC discussions, transition to comfort measures only (CMO), and the utilization of specialty palliative services were analyzed with univariate analysis. RESULTS: During the study period, 415 inpatients died. Median Injury Severity Score was 26 (interquartile range [IQR], 17–34), median age was 67 years (IQR, 51–81 years), and 72% (n = 299) transitioned to CMO before death. Documented GOC discussions increased from 77% of patients in 2014 to 95% of patients in 2018 ( p < 0.001), and in 2018, the median time to the first GOC discussion was 15 hours (IQR, 7– 24 hours). Specialty palliative care was consulted in 7% of all patients. Of patients who had at least one GOC discussion, 98% were led by the trauma intensive care unit (TICU) team. Median time from admission to first GOC discussion was 27 hours (IQR, 6–91 hours). Median number of GOC discussions was 1 (IQR, 1–2). Median time to CMO after the final GOC discussion was 0 hours (IQR, 0–3). Median time to death after transition to CMO was 4 hours (IQR, 1–18 hours). CONCLUSION: Of those who died during index admission, we demonstrated significant improvement in adherence to American College of Surgeons TQIP palliative guidelines across the 5-year study period, with the TICU team guiding the majority of GOC discussions. Our TICU team has developed an effective primary palliative care approach, selectively consulting specialty palliative care only when needed. LEVEL OF EVIDENCE: Therapeutic/care management, level III.